GAMBARAN STATUS, DERAJAT DAN PROFIL MEROKOK SERTA KETERGANTUNGAN NIKOTIN PADA PASIEN PEROKOK YANG DIRAWAT DI BANGSAL PARU RSUP DR. M. DJAMIL PADANG - Sur Yastri; Sabrina Ermayanti; Russi lawati (HUMAN CARE JOURNAL, 2019)
Smoking was still health major problem in the word that lead 7.1 million smoking related deaths annually. Prevalence smoking in Indonesia was fifth in the world. Based on Riskesdas in 2007 and 2010 showed an increase number of smokers from 29% - 34.7%. Methods: This is Descriptive-prospective study in 177 patients who were treated in pulmonary ward of Dr. M. Djamil Padang from November 2016 to January 31, 2017. Data were collected through interviews patients with closed questions and validated questioner. Results: This study found total 177 patients that consist of 128 (72.4%) males with an average age of 52.5 ± 15.57 SD years. History of smoking were 63 smokers (35.6%), 67 nonsmokers (37.8%) and former smokers 47 (26.5%). Smoker patients have been found most in bronchogenic carcinoma patients 24 (38%), with profile for stress 34 (54%), and the Brinkman index grade was severe. Former smokers were mostly in patients with pneumonia 11 (23.4%) and COPD 10 (21.2%). The nicotine dependence is low to moderate 13 (56.5%) in patients with bronchogenic carcinoma and low dependence 10 (53%) in TB patients. Conclusion: Patients that were treated in the pulmonary ward more than third were smokers. The most common profile was for pleasure and nicotine dependence mostly low to moderate could give opportunity for educational intervention.